Emulsion stability enhancement against environmental stresses using whey protein–tragacanthin complex: Comparison of layer-by-layer and mixing methods. (29th December 2017) - Azarikia, Fatemeh; Abbasi, Soleiman; Scanlon, Martin G; McClements, David J
ABSTRACT: There are two known techniques as emulsion preparation methods in which oppositely charged biopolymers are attached to each other via electrostatic interaction at oil–water interface: Layer by layer (LBL) and mixed methods. The aim of this research was to compare the stability of emulsions prepared by these methods against environmental stresses (heating, salt addition and freeze–thaw) when the oil droplets covered with whey protein isolate and tragacanthin. The presence of tragacanthin improved stability of both mixed and LBL emulsions against heat treatments under 100°C. LBL emulsions also showed better stability against various ionic strengths and freeze–thaw treatments.